Preparation and characterisation of activated carbon from waste tea by using sodium hydroxide for adsorption of methylene blue / Zaidatulhusna Zulkurnain - Zulkurnain, Zaidatulhusna (2022)
The adsorption performance of activated carbon prepared from treated waste tea by using NaOH for removal of methylene blue (MB) dye from aqueous solution was investigated. A batch adsorption study was conducted to observe the effect of different adsorption parameters on the adsorption capacity. This experiment was performed under operating condition of adsorbent dosage: 0.225g, pH 8 at room temperature. Based on the result, the equilibrium of adsorption increased with the increasing of initial concentration of MB. The yield percentage was 74.35% and the pHpzc surface value is 6.2. The optimum initial pH and MB concentration were pH 8 and 20 mg/L, respectively. The percentage removal of MB increased by decreasing the initial concentration of MB at constant dosage and the effect of temperature showed that the adsorption capacity increase with the increase of these parameters. The optimum temperature was obtained at 500°C. Thus, it is approved that this cost-effective adsorbent has a great potential for the removal of MB dye in the aqueous solution.